Model Peningkatan Kinerja Sumber Daya Manusia melalui Pembelajaran Organisasional dan Motivasi Intrinsik di Sekretariat Daerah Kabupaten Kotawaringin Barat - Fibriantoro, Dedy; Sulistyo, Heru (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The purpose of this study is to analyze the influence of Organizational Learning variables, and Intrinsic Motivation on improving Human Resource Performance, The data used in this study are primary data in the form of questionnaires totaling 179 respondents from the Regional Secretariat Employees of West Kotawaringin Regency. consisting of ASN both PNS and PPPK and Regional Contract Workers. The sampling technique used in this study is a census or saturated sampling technique. This study was analyzed using the Structural Equation Modeling technique based on Partial Least Square (SEM-PLS) version 3.2.9 to facilitate processing the data obtained. In analyzing the data, the validity (discriminant validity and convergent validity) and reliability were first tested using Partial Least Square (PLS). The results of the study indicate that (1) Organizational learning has a positive effect on human resource performance, (2) Intrinsic motivation has a positive effect on human resource performance, (3) Organizational learning has a positive effect on intrinsic motivation, (4) Organizational learning mediated by intrinsic motivation has a positive effect on human resource performance, in this study, of the 3 variables that have the greatest influence in relation to each other. Namely the Organizational Learning variable with a magnitude of 0.648. This shows that human resources in the Regional Secretariat of West Kotawaringin Regency actually want the implementation of organizational learning, meaning that the higher the Organizational Learning that is implemented, the more it will have an impact on increasing the value of Intrinsic Motivation, where this will then increase the value of human resource performance produced for the agency.